Pemahaman dan Persepsi Penyuluh Perikanan terhadap Penggunaan Teknologi Informasi dan Komunikasi dalam Penyuluhan di Kota Bandar Lampung - Ayu Nirmala Lutfie Syarief; Helvi Yanfika; Abdul Mutolib (Ethos: Jurnal Penelitian dan Pengabdian kepada Masyarakat, 2021)
Abstract. This study aims to determine the energy of fisheries extension, internet understanding by extension fisheries and perceptions fisheries extension of the use of technology information and communication in extension.  this research was conducted in the city of Bandar Lampung.  This study used a purposive sampling technique.  Fisheries extension amount of  12 people in the city of Bandar Lampung.  The type of data used in this study are primary and secondary data.  The method used in this research is a descriptive qualitative. The results of the study found that the employment of fisheries extension still did not ideally in every sub-district in Bandar Lampung City.  Understanding of internet fisheries extension in the city of Bandar Lampung is still quite low.  Likewise, the perception fisheries extension of the use technology information and communication seen from the purpose of using ICT in good category. The perception fisheries extension on the use technology information and communication seen from the benefits of ICTs in good category.. Another case, perception fisheries extension of the use technology information and communication seen from the implementation of extension using ICTs in the poor category.